Language learning strategies and communicative competence of Colombian learners of English as a foreign language - Marenco Domínguez, José Miguel; Angel-Cuervo, Zaida Mabel; Dávila Rubio, Carlos Alberto; Latorre Méndez, Dany Andrey; Quevedo-Padilla, Laura Bibiana (Journal of Education and Learning (EduLearn), 2025)
Even when proficiency in foreign languages has emerged as a critical skill to foster academic, professional, and personal growth, there remains a notable gap in the literature regarding the relation between language learning strategies (LLS) and communicative competence in English among Colombian high school students. This investigation used an explanatory correlational design to explore the connections between LLS and the communicative competence of 123 eleventh graders within the Colombian context. Data collected employing an inventory and the results of the English section of a standardized test in Colombia were subjected to analysis. The findings suggest that students favor social strategies, whereas affective strategies are used to a lesser extent. Additionally, there is a moderate positive correlation between the overall use of LLS and learners’ communicative competence in English. Particularly, cognitive and metacognitive strategies emerged as the strategies that contribute most significantly to students’ language proficiency. Conversely, memory and affective strategies were found to have the weakest correlation with learners’ language learning success. This study accentuates the importance of strategies-based instruction to boost language proficiency and outlines recommendations for future research.